2022
DOI: 10.17221/127/2022-pse
|View full text |Cite
|
Sign up to set email alerts
|

Soil enzyme activities after application of fungicide Quadris<sup>R</sup> at increasing concentration rates

Abstract: The study aimed to assess the effects of fungicide QuadrisR on activities of soil enzymes contributed to soil nutrient turnover. A batch laboratory experiment with QuadrisR-amended (0 mg/kg ds (dry soil) – 35.00 mg/kg ds) loamy sand soil was conducted, and shifts in soil physical environments and enzyme activities (beta-glucosidase, urease, acid and alkaline phosphatases, arylsulfatase and dehydrogenase) were evaluated on experimental days 1, 30, 60, 90 and 120. The results indicated that QuadrisR changed both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…They also contribute to reducing the activity of catalase in the soil, which protects cells from toxic H 2 O 2 produced in the cytoplasm and peroxisomes, and which is sensitive to various environmental stressors [55,56]. Additionally, fungicides may affect soil acidification, most likely due to their chemical composition or via chemical reactions occurring in the soil, but also disruptions in the biological balance of the soil [57]. Numerous studies have reported the reduction in enzyme activity, especially dehydrogenases, but also catalase, urease, alkaline phosphatase, and protease, with increasing soil acidification [58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…They also contribute to reducing the activity of catalase in the soil, which protects cells from toxic H 2 O 2 produced in the cytoplasm and peroxisomes, and which is sensitive to various environmental stressors [55,56]. Additionally, fungicides may affect soil acidification, most likely due to their chemical composition or via chemical reactions occurring in the soil, but also disruptions in the biological balance of the soil [57]. Numerous studies have reported the reduction in enzyme activity, especially dehydrogenases, but also catalase, urease, alkaline phosphatase, and protease, with increasing soil acidification [58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance of the products was measured using a spectrophotometer (Specord 200 plus, Analytic Jena, Germany). Acid and alkaline phosphatase activity of the soil was evaluated by the method of Tabatabai and Bremner, 1969 ; Boteva et al., 2022 . Toluene solution modified universal buffer, 0.5 ml CaCl 2 was added in soil and swirled.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, nitrogen has been recognized as the primary nutrient limiting crop yield in various agro-ecological regions [30,31]. Nitrogen fertilizer has a significant impact on the physiological aspects of plants, including respiration rate, water balance, signaling pathways, overall growth and development [32][33][34]. Recent research has shown that applying fertilizers containing phosphorus (P) and potassium (K) together can enhance the uptake of nitrogen (N) fertilizers and improve N efficiency [35].…”
Section: Introductionmentioning
confidence: 99%